Détermination rapide et spécifique du taux dhydrolyse du lactose par méthode enzymatique et HPLC. - TAKARLI, HAYET (My University, 2018)
Lactose intolerance is caused by lactose deficiency. Lactose not transformed by lactase is found in the intestine where it ferments and causes digestive symptoms. People with lactose intole-rance often feel better when they add lactase enzymes to their diet. And for this reason we decided to make a lactose-free milk for lactose intolerants. In this research three different en-zymes (Maxilact, Nola fit, Ha-lactase) are used and the hydrolyzed lactose level is determined by a classical HPLC method and enzymatic method using a K-lolac kit. According to the results; Maxilact at a dose of 1000μl gives very good results compared to Ha-lactase and Nola fit . and concerning Maxilact and Nola in the case of different dose, Maxilact at 500 μl dose the remai-ning amount of lactose and better compared to Nola made, on the other hand at dose from 1500μl to 2000μl Nola hydrolyses better than Maxilact and concerning the methods used to determine the lactose level the best method is the enzymatic method (Kit K-lolac megazyme) because the enzymatic method detects small dose of lactose
Keywords: Lactose; lactase; lactose intolerance; enzyme method; HPLC; intolérance au lactose; méthode enzymatique